Preparation method of positive electrode of lithium battery and lithium battery

The carbon fiber membrane is prepared by static spinning and the load nanosulfulus particles are used to filter the load, which solves the problem of low lithium sulfur system orthopedic conductivity and volume expansion, and achieves higher conductivity and structural stability.

CN119361609AActive Publication Date: 2025-01-24DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411541272.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The positive electrode of the lithium sulfur system has problems of low conductivity and volume expansion, which hinders its application in lithium batteries.

Method used

The carbon fiber membrane is prepared by electrospinning, and the carbon fiber membrane is used as a carrier to load nano-sulfur particles through suction filtration, so that the nano-sulfur particles are deposited in the gaps between the carbon fibers.

Benefits of technology

The cathode conductivity of the lithium-sulfur system is improved, the destructive effect of volume expansion on the cathode structure is alleviated, the operation is simplified, and the morphology of sulfur is controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361609A_ABST
    Figure CN119361609A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a lithium battery positive electrode and a lithium battery, and relates to the field of new energy, the preparation method of the lithium battery positive electrode comprises the following steps: preparing a fiber membrane through electrostatic spinning by taking a carbonizable polymer as a material; performing heat treatment on the fiber membrane to obtain a carbon fiber membrane; providing a nano sulfur particle suspension and a binder solution, and carrying out suction filtration treatment on the nano sulfur particle suspension and the binder solution by taking the carbon fiber membrane as a filter membrane to obtain a prefabricated positive electrode; and drying the prefabricated positive electrode to obtain the lithium battery positive electrode. According to the present invention, the large buffer space is provided for the volume change during the mutual conversion process of sulfur and lithium sulfide, and the problem of low conductivity of the positive electrode of the lithium-sulfur system can be effectively improved. In addition, the suction filtration treatment also has the advantages of simple operation and easy control of the shape of sulfur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy, and in particular to lithium batteries. Background Art

[0002] The energy density of lithium-ion batteries with ternary and lithium iron phosphate as positive electrodes is currently close to the theoretical value, reaching the bottleneck of technological development. In order to solve the range anxiety of electric vehicles, it is urgent to develop a new battery system with high energy density. Lithium-sulfur batteries have a theoretical energy density of up to 2600Wh / kg, which is several times that of ternary systems. However, the conductivity of the active material sulfur and the discharge end product lithium sulfide in the lithium-sulfur system is low, resulting in more serious battery polarization; the density of the active material sulfur is about 2.07g / cm 3 The density of the final discharge product, lithium sulfide, is about 1.66 g / cm 3 , resulting in about 80% volume expansion during charge and discharge, which can easily have a destructive effect on the positive electrode structure. The technical problems of low conductivity and volume expansion of the positive electrode of the lithium-sulfur system hinder its application in lithium batteries. Summary of the invention

[0003] The embodiments of the present application provide a method for preparing a positive electrode of a lithium battery and a lithium battery to solve the technical problems of low conductivity and volume expansion of the positive electrode of a lithium-sulfur system.

[0004] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode of a lithium battery, the method for preparing a positive electrode of a lithium battery comprising the following steps:

[0005] Using carbonizable polymer as material, fiber membrane is prepared by electrospinning;

[0006] heat-treating the fiber membrane to obtain a carbon fiber membrane;

[0007] Providing a nano-sulfur particle suspension and a binder solution, and using the carbon fiber membrane as a filter membrane to perform suction filtration on the nano-sulfur particle suspension and the binder solution to obtain a prefabricated positive electrode;

[0008] The prefabricated positive electrode is dried to obtain the positive electrode of the lithium battery.

[0009] In some embodiments of the present application, the polymer material is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,

[0010] The solvent of the electrospinning solution used in the electrospinning is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,

[0011] In the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:5-12.

[0012] In some embodiments of the present application, the electrospinning is performed through at least one spinneret, and on average for each spinneret, the process parameters of the electrospinning meet the following conditions:

[0013] Voltage is 12~20kV;

[0014] The spinning solution flow rate is 0.6-1.5 mL / h;

[0015] The receiving distance is 12 to 20 cm.

[0016] In some embodiments of the present application, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially.

[0017] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 200-300° C.; and / or,

[0018] The pre-oxidation treatment time is 0.5 to 1 hour; and / or,

[0019] The pre-oxidation treatment is carried out in an oxygen-containing atmosphere; and / or,

[0020] The temperature of the carbonization treatment is 700-900° C.; and / or,

[0021] The carbonization treatment time is 1 to 3 hours; and / or,

[0022] The carbonization treatment is performed in an inert atmosphere.

[0023] In some embodiments of the present application, in the nano-sulfur particle suspension, the mass ratio of the solvent to the nano-sulfur particles in the nano-sulfur particle suspension is 1:1.5-4; and / or,

[0024] The solvent of the nano-sulfur particle suspension includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.

[0025] In some embodiments of the present application, the nano-sulfur particle suspension further includes a conductive agent and a surfactant.

[0026] In some embodiments of the present application, the conductive agent is at least one of acetylene black and conductive carbon black; and / or,

[0027] In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:9-50; and / or the surfactant is at least one of cetyltrimethylammonium bromide, polyvinylpyrrolidone and Triton.

[0028] In some embodiments of the present application, the binder is at least one of polyvinyl pyrrolidone, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, and carboxymethyl cellulose; and / or,

[0029] The solvent of the binder solution is at least one of N-methylpyrrolidone and N,N-dimethylformamide; and / or,

[0030] In the binder solution, the mass fraction of the binder is 0.5% to 1%.

[0031] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium battery positive electrode prepared by the method described in any embodiment of the first aspect.

[0032] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0033] The preparation method of the positive electrode of a lithium battery provided in an embodiment of the present application is to prepare a carbon fiber membrane having the structural characteristics of an electrostatic spinning fabric by heat treatment of an electrostatic spinning fabric, and then use the carbon fiber membrane as a carrier to load nano-sulfur particles through suction filtration, so that the nano-sulfur particles are deposited in the gaps between the carbon fibers of the carbon fiber membrane during the suction filtration process. The abundant gaps between the carbon fibers and the good bending and changing ability of the carbon fibers themselves provide a large buffer space for the volume change during the mutual conversion of sulfur and lithium sulfide. The large specific surface area of ​​the carbon fiber membrane provides abundant contact sites for sulfur or lithium sulfide, which can effectively improve the problem of low positive electrode conductivity of the lithium-sulfur system. In addition, the suction filtration process also has the advantages of simple operation and easy control of the morphology of sulfur. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0035] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0036] Figure 1 A schematic flow chart of a method for preparing a positive electrode of a lithium battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0038] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] The positive electrode of the existing lithium-sulfur system has technical problems of low conductivity and volume expansion.

[0041] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:

[0042] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode of a lithium battery, the method for preparing a positive electrode of a lithium battery comprising the following steps:

[0043] S1: Using carbonizable polymer as material, fiber membrane is prepared by electrospinning;

[0044] S2: heat-treating the fiber membrane to obtain a carbon fiber membrane;

[0045] S3: providing a nano-sulfur particle suspension and a binder solution, and using the carbon fiber membrane as a filter membrane to filter the nano-sulfur particle suspension and the binder solution to obtain a prefabricated positive electrode;

[0046] S4: drying the prefabricated positive electrode to obtain the lithium battery positive electrode.

[0047] It is easy to understand that in electrospun fabrics, there are usually large gaps between fibers, and the electrospun fabric itself has a large specific surface area. The carbon fiber membrane described in the present application is made by heat-treating the fiber membrane, and the fiber membrane is an electrospun fabric, which makes the carbon fiber membrane also have the structural characteristics of the electrospun fabric.

[0048] The present application uses suction filtration to deposit nano-sulfur particles in the gaps between the carbon fibers of the carbon fiber membrane during the filtration process. When the positive electrode of the lithium battery is charged and discharged, the surface of the carbon fiber will also simultaneously undergo a reaction of mutual conversion between sulfur and lithium sulfide. The abundant gaps between the carbon fibers and the good bending and changeability of the carbon fibers themselves provide a large buffer space for the volume change during the mutual conversion between sulfur and lithium sulfide. The large specific surface area of ​​the carbon fiber membrane provides abundant contact sites for sulfur or lithium sulfide, which can effectively improve the problem of low positive electrode conductivity of the lithium-sulfur system.

[0049] The present invention also has several beneficial effects of loading the nano-sulfur particles onto the carbon fiber membrane by suction filtration. Firstly, the operation of suction filtration is very simple; secondly, compared with electrodeposition and hot melt casting, suction filtration can control the morphology of sulfur into nano-sulfur particles by selecting a nano-sulfur particle suspension as a raw material.

[0050] The present application prepares a carbon fiber membrane having the structural characteristics of an electrostatically spun fabric by heat treating an electrostatically spun fabric, and then uses the carbon fiber membrane as a carrier to carry nano-sulfur particles through suction filtration, so that the nano-sulfur particles are deposited in the gaps between the carbon fibers of the carbon fiber membrane during suction filtration. The abundant gaps between the carbon fibers and the good bending and changing ability of the carbon fibers themselves provide a large buffer space for the volume change during the mutual conversion of sulfur and lithium sulfide. The large specific surface area of ​​the carbon fiber membrane provides abundant contact sites for sulfur or lithium sulfide, which can effectively improve the problem of low positive electrode conductivity of the lithium-sulfur system. In addition, the suction filtration process also has the advantages of simple operation and easy control of the morphology of sulfur.

[0051] In some embodiments of the present application, the polymer material is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,

[0052] The solvent of the electrospinning solution used in the electrospinning is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,

[0053] In the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:5-12.

[0054] It is easy to understand that the above-mentioned polymer materials are all suitable for electrospinning technology, and are raw materials with good electrospinning effects. Moreover, the above-mentioned polymer materials can be easily carbonized to form carbon fibers through heat treatment.

[0055] The beneficial effect of the mass ratio of the polymer material to the solvent of the electrospinning solution being 1:5-12 is that it ensures that the fibers formed by electrospinning can be well formed and that the polymer material can be fully dispersed in the electrospinning solution.

[0056] As an example, the mass ratio of the polymer material to the solvent of the electrospinning solution may be 1:5, 1:7, 1:9, 1:10, or 1:12.

[0057] In some embodiments of the present application, the electrospinning is performed through at least one spinneret, and on average for each spinneret, the process parameters of the electrospinning meet the following conditions:

[0058] Voltage is 12~20kV;

[0059] The spinning solution flow rate is 0.6-1.5 mL / h;

[0060] The receiving distance is 12 to 20 cm.

[0061] It is easy to understand that the beneficial effect of the voltage of 12-20 kV is that the fibers produced by electrospinning have a smaller diameter while ensuring the formation of the fibers. The beneficial effect of the spinning solution flow rate of 0.6-1.5 mL / h is to ensure the efficiency of electrospinning and the formation of the fibers.

[0062] It is easy to understand that the receiving distance is the distance between the outlet end of the electrospinning solution of the spinneret and the fiber receiving device. The beneficial effects of a receiving distance of 12 to 20 cm are: ensuring sufficient electric field strength during the electrospinning process; ensuring that the displacement distance of the electrospinning solution to the fiber receiving device is appropriate, so that the fiber receiving device can smoothly collect the fiber, and also allowing the solvent to fully evaporate during the movement of the electrospinning solution.

[0063] As an example, the voltage may be 12 kV, 14 kV, 16 kV, 18 kV, 20 kV.

[0064] As an example, the spinning solution flow rate may be 0.6 mL / h, 0.8 mL / h, 1 mL / h, 1.3 mL / h, 1.5 mL / h;

[0065] As an example, the receiving distance may be 12 cm, 14 cm, 16 cm, 18 cm, or 20 cm.

[0066] In some embodiments of the present application, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially.

[0067] It is easy to understand that the purpose of the pre-oxidation treatment is to introduce oxygen-containing groups into the fiber membrane so that there are sufficient oxygen atoms involved in the subsequent carbonization treatment, thereby making the carbonization treatment more sufficient and thorough.

[0068] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 200-300° C.; and / or,

[0069] The pre-oxidation treatment time is 0.5 to 1 hour; and / or,

[0070] The pre-oxidation treatment is carried out in an oxygen-containing atmosphere; and / or,

[0071] The temperature of the carbonization treatment is 700-900° C.; and / or,

[0072] The carbonization treatment time is 1 to 3 hours; and / or,

[0073] The carbonization treatment is performed in an inert atmosphere.

[0074] It is easy to understand that the beneficial effect of the pre-oxidation treatment temperature being 200-300° C. is that it can effectively introduce oxygen-containing groups into the fiber membrane without destroying the structure of the fibers in the fiber membrane.

[0075] It is easy to understand that the beneficial effect of the pre-oxidation treatment time of 0.5 to 1 hour is that it can effectively introduce oxygen-containing groups into the fiber membrane without destroying the structure of the fibers in the fiber membrane.

[0076] It is easy to understand that the beneficial effect of the carbonization treatment temperature being 700-900° C. is to save energy as much as possible while ensuring the carbonization effect.

[0077] It is easy to understand that the beneficial effect of the carbonization treatment time of 1 to 3 hours is to save energy as much as possible while ensuring the carbonization effect.

[0078] As an example, the temperature of the pre-oxidation treatment is 200°C, 220°C, 240°C, 260°C, 280°C, or 300°C.

[0079] As an example, the pre-oxidation treatment time is 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, and 0.1h.

[0080] As an example, the oxygen-containing atmosphere may be air.

[0081] As an example, the temperature of the carbonization treatment may be 700°C, 750°C, 800°C, 850°C, or 900°C.

[0082] As an example, the carbonization treatment time can be 1 h, 1.5 h, 2 h, 2.5 h, or 3 h.

[0083] As an example, the inert atmosphere may be argon or nitrogen.

[0084] In some embodiments of the present application, in the nano-sulfur particle suspension, the mass ratio of the solvent to the nano-sulfur particles in the nano-sulfur particle suspension is 1:1.5-4; and / or,

[0085] The solvent of the nano-sulfur particle suspension includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.

[0086] It is easy to understand that the beneficial effect of the mass ratio of the solvent to the nano-sulfur particles in the nano-sulfur particle suspension being 1:1.5-4 is that the nano-sulfur particles can be fully dispersed in the nano-sulfur particle suspension while ensuring a high concentration of the nano-sulfur particles, so that the nano-sulfur particles can be quickly deposited on the carbon fiber membrane during the filtration process.

[0087] As an example, the mass ratio of the solvent to the nano-sulfur particles in the nano-sulfur particle suspension may be 1:1.5, 1:2, 1:2.5, 1:3, or 1:4.

[0088] In some embodiments of the present application, the nano-sulfur particle suspension further includes a conductive agent and a surfactant.

[0089] In some embodiments of the present application, the conductive agent is at least one of acetylene black and conductive carbon black; and / or,

[0090] In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:9-50; and / or the surfactant is at least one of cetyltrimethylammonium bromide, polyvinylpyrrolidone and Triton.

[0091] It is easy to understand that the beneficial effect of the mass ratio of the conductive agent to the nano-sulfur particles being 1:9-50 is that the conductivity of the nano-sulfur particles can be increased as much as possible, while the amount of the nano-sulfur particles as the active positive electrode material is sufficient.

[0092] As an example, the mass ratio of the conductive agent to the nano-sulfur particles can be 1:9, 1:20, 1:30, 1:40, or 1:50.

[0093] In some embodiments of the present application, the binder is at least one of polyvinyl pyrrolidone, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, and carboxymethyl cellulose; and / or,

[0094] The solvent of the binder solution is at least one of N-methylpyrrolidone and N,N-dimethylformamide; and / or,

[0095] In the binder solution, the mass fraction of the binder is 0.5% to 1%.

[0096] As an example, the mass fraction of the binder may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%.

[0097] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium battery positive electrode prepared by the method described in any embodiment of the first aspect.

[0098] The lithium battery is realized based on the lithium battery positive electrode described in any embodiment of the first aspect. The specific implementation of the lithium battery can refer to the above embodiments and common knowledge in the field. Since the lithium battery adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0099] The present application will be further described below in conjunction with specific examples. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards. If there is no corresponding industry standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0100] Example 1

[0101] The present invention provides a method for preparing a positive electrode of a lithium battery, and the method for preparing a positive electrode of a lithium battery comprises the following steps:

[0102] Sa: Carbonizable polymers are used as materials to prepare fiber membranes by electrospinning;

[0103] Sb: pre-oxidizing and carbonizing the fiber membrane to obtain a carbon fiber membrane;

[0104] Sc: providing a nano-sulfur particle suspension and a binder solution, using the carbon fiber membrane as a filter membrane, dropping the nano-sulfur particle suspension onto the carbon fiber membrane for suction filtration, and then dropping the binder solution onto the carbon fiber membrane for suction filtration to obtain a prefabricated positive electrode;

[0105] Sd: Drying the prefabricated positive electrode to obtain the lithium battery positive electrode.

[0106] Wherein, the polymer material is polyvinyl alcohol, the solvent of the electrospinning solution used for the electrospinning is water, and in the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:9.

[0107] The temperature of the pre-oxidation treatment is 250° C., the time of the pre-oxidation treatment is 0.8 h, and the pre-oxidation treatment is carried out in air. The temperature of the carbonization treatment is 800° C., the time of the carbonization treatment is 2 h, and the carbonization treatment is carried out in nitrogen.

[0108] In the nano-sulfur particle suspension, the mass ratio of the solvent of the nano-sulfur particle suspension to the nano-sulfur particles is 1:1.5, and the solvent of the nano-sulfur particle suspension is N-methylpyrrolidone.

[0109] The nano-sulfur particle suspension also includes a conductive agent and a surfactant. The conductive agent is acetylene black. In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:9. The surfactant is hexadecyltrimethylammonium bromide.

[0110] The binder is polyvinylidene fluoride, the solvent of the binder solution is N-methylpyrrolidone, and the mass fraction of the binder in the binder solution is 0.5%.

[0111] The electrospinning is performed by a single spinneret, and the process parameters of the electrospinning meet the following conditions:

[0112] The voltage is 12kV;

[0113] The spinning solution flow rate was 0.6 mL / h;

[0114] The receiving distance is 12cm.

[0115] Example 2

[0116] The present invention provides a method for preparing a positive electrode of a lithium battery, and the method for preparing a positive electrode of a lithium battery comprises the following steps:

[0117] Sa: Carbonizable polymers are used as materials to prepare fiber membranes by electrospinning;

[0118] Sb: pre-oxidizing and carbonizing the fiber membrane to obtain a carbon fiber membrane;

[0119] Sc: providing a nano-sulfur particle suspension and a binder solution, using the carbon fiber membrane as a filter membrane, dropping the nano-sulfur particle suspension onto the carbon fiber membrane for suction filtration, and then dropping the binder solution onto the carbon fiber membrane for suction filtration to obtain a prefabricated positive electrode;

[0120] Sd: Drying the prefabricated positive electrode to obtain the lithium battery positive electrode.

[0121] Wherein, the polymer material is polyacrylonitrile, the solvent of the electrospinning solution used for the electrospinning is NN dimethylformamide, and in the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:5.

[0122] The pre-oxidation treatment was carried out at a temperature of 200° C. for 1 hour in air. The carbonization treatment was carried out at a temperature of 700° C. for 3 hours in nitrogen.

[0123] In the nano-sulfur particle suspension, the mass ratio of the solvent of the nano-sulfur particle suspension to the nano-sulfur particles is 1:4, and the solvent of the nano-sulfur particle suspension is N,N-dimethylformamide.

[0124] The nano-sulfur particle suspension also includes a conductive agent and a surfactant. The conductive agent is conductive carbon black. In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:50. The surfactant is polyvinyl pyrrolidone.

[0125] The binder is polyvinylidene fluoride, the solvent of the binder solution is N-methylpyrrolidone, and the mass fraction of the binder in the binder solution is 1%.

[0126] The electrospinning is performed by a single spinneret, and the process parameters of the electrospinning meet the following conditions:

[0127] The voltage is 20kV;

[0128] The spinning solution flow rate was 1.5 mL / h;

[0129] The receiving distance is 20cm.

[0130] Example 3

[0131] The present invention provides a method for preparing a positive electrode of a lithium battery, and the method for preparing a positive electrode of a lithium battery comprises the following steps:

[0132] Sa: Carbonizable polymers are used as materials to prepare fiber membranes by electrospinning;

[0133] Sb: pre-oxidizing and carbonizing the fiber membrane to obtain a carbon fiber membrane;

[0134] Sc: providing a nano-sulfur particle suspension and a binder solution, using the carbon fiber membrane as a filter membrane, dropping the nano-sulfur particle suspension onto the carbon fiber membrane for suction filtration, and then dropping the binder solution onto the carbon fiber membrane for suction filtration to obtain a prefabricated positive electrode;

[0135] Sd: Drying the prefabricated positive electrode to obtain the lithium battery positive electrode.

[0136] Wherein, the polymer material is polyurethane, the solvent of the electrospinning solution used for the electrospinning is acetone, and in the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:7.

[0137] The pre-oxidation treatment was carried out at a temperature of 300° C. for a time of 0.5 h in air. The carbonization treatment was carried out at a temperature of 900° C. for a time of 1 h in nitrogen.

[0138] In the nano-sulfur particle suspension, the mass ratio of the solvent of the nano-sulfur particle suspension to the nano-sulfur particles is 1:2, and the solvent of the nano-sulfur particle suspension is N,N-dimethylformamide.

[0139] The nano-sulfur particle suspension also includes a conductive agent and a surfactant. The conductive agent is acetylene black. In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:20, and the surfactant is Triton.

[0140] The binder is carboxymethyl cellulose, the solvent of the binder solution is N,N-dimethylformamide, and the mass fraction of the binder in the binder solution is 0.8%.

[0141] The electrospinning is performed by a single spinneret, and the process parameters of the electrospinning meet the following conditions:

[0142] The voltage is 15kV;

[0143] The spinning solution flow rate was 0.9 mL / h;

[0144] The receiving distance is 15cm.

[0145] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0146] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively. The "number of parts" involved in this application, such as weight parts, mass parts, etc., represent the proportional relationship between each component. In the proportional relationship involved in the present application, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0147] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a positive electrode of a lithium battery, characterized in that: The method for preparing the positive electrode of the lithium battery comprises the following steps: Using carbonizable polymer as material, fiber membrane is prepared by electrospinning; heat-treating the fiber membrane to obtain a carbon fiber membrane; Providing a nano-sulfur particle suspension and a binder solution, and using the carbon fiber membrane as a filter membrane to perform suction filtration on the nano-sulfur particle suspension and the binder solution to obtain a prefabricated positive electrode; The prefabricated positive electrode is dried to obtain the positive electrode of the lithium battery.

2. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: The polymer material is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or, The electrospinning solution used in the electrospinning process is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol and hexafluoroisopropanol; and / or, In the electrospinning solution used for the electrospinning, the mass ratio of the polymer material to the solvent of the electrospinning solution is 1:5-12.

3. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: The electrospinning is performed through at least one spinneret, and the process parameters of the electrospinning meet the following conditions on average for each spinneret: Voltage is 12~20kV; The spinning solution flow rate is 0.6-1.5 mL / h; The receiving distance is 12 to 20 cm.

4. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: The heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially.

5. The method for preparing a positive electrode of a lithium battery according to claim 4, characterized in that: The temperature of the pre-oxidation treatment is 200-300° C.; and / or, The pre-oxidation treatment time is 0.5 to 1 hour; and / or, The pre-oxidation treatment is carried out in an oxygen-containing atmosphere; and / or, The temperature of the carbonization treatment is 700-900° C.; and / or, The carbonization treatment time is 1 to 3 hours; and / or, The carbonization treatment is performed in an inert atmosphere.

6. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: In the nano-sulfur particle suspension, the mass ratio of the solvent to the nano-sulfur particles in the nano-sulfur particle suspension is 1:1.5-4; and / or, The solvent of the nano-sulfur particle suspension includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.

7. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: The nano sulfur particle suspension also includes a conductive agent and a surfactant.

8. The method for preparing a positive electrode of a lithium battery according to claim 7, characterized in that: The conductive agent is at least one of acetylene black and conductive carbon black; and / or, In the nano-sulfur particle suspension, the mass ratio of the conductive agent to the nano-sulfur particles is 1:9-50; and / or, The surfactant is at least one of cetyltrimethylammonium bromide, polyvinylpyrrolidone and Triton.

9. The method for preparing a positive electrode of a lithium battery according to claim 1, characterized in that: The binder is at least one of polyvinyl pyrrolidone, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber and carboxymethyl cellulose; and / or, The solvent of the binder solution is at least one of N-methylpyrrolidone and N,N-dimethylformamide; and / or, In the binder solution, the mass fraction of the binder is 0.5% to 1%.

10. A lithium battery, characterized in that: The lithium battery comprises a lithium battery positive electrode prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode-forming member, material for the same, method for producing the same, and lithium ion secondary battery

    CN101682025A

  • Flexible high-sulfur load self-repairing cathode structure for lithium-sulfur battery and preparation method of flexible high-sulfur load self-repairing cathode structure

    CN105098143A

  • Silicon negative electrode composite material for lithium-ion battery and preparation method thereof

    CN106025243A

  • Porous carbon nanofiber and preparation method thereof and lithium-sulfur battery

    CN110158200A

  • Lithium-sulfur battery self-supporting cathode material and electro-spinning preparation method thereof

    CN110438798A

Cited By

  • High-performance porous soft and hard carbon fiber negative electrode material for lithium ion battery and preparation method of high-performance porous soft and hard carbon fiber negative electrode material

    CN120042001A